Effects of continuous positive airway pressure on fatigue in two patients with obstructive sleep apnea presenting with chronic fatigue: case report and lessons learned from a failed trial. Issue 6 (2nd November 2017) - Tobback, Els; Delesie, Liesbeth; Hanoulle, Ignace; Vogelaers, Dirk; Pevernagie, Dirk; Mariman, An
Abstract : Introduction: Patients referred to tertiary care for multidisciplinary investigation of unexplained chronic fatigue are not seldom diagnosed with obstructive sleep apnoea (OSA). As standard treatment for OSA, continuous positive airway pressure (CPAP) has been shown to decrease daytime sleepiness in OSA patients. However, the effect on fatigue as major complaint in chronic fatigue patients without excessive daytime sleepiness, is not fully understood nor explored. Case report: A prospective cross-over trial using effective and sham CPAP treatment periods in patients with unexplained chronic fatigue and OSA was interrupted because of poor recruitment and retainment due to complex design issues. We report the effect of CPAP after one month and one to two years follow-up on fatigue as primary outcome and on daytime sleepiness, global sleep quality and global mental and physical health as secondary outcomes in two patients completing the trial. In both patients, comparison of sequential effective and sham CPAP treatments failed to demonstrate consistent short-term effects in outcome measures, in spite of significant differences in apnoea-hypopnea index. However, substantial improvements of fatigue scores were observed at long-term follow-up in both individuals. Conclusion: This is the first report of both short- and long-term effects of CPAP treatment on fatigue in patients with OSA and disabling chronic fatigue as primary complaint. A feasible prospective trial remains warranted in order to answer the question of CPAP responsiveness of fatigue in this patient population.